Analysis of Vocational School Students' Ability in Conceptual Understanding - Riskana Br Sitepu; Ani Rusilowati; Bambang Subali; Ahmad Sukron Khafifi (JIPF (Jurnal Ilmu Pendidikan Fisika), 2019)
The purpose of this study was to analyze the ability of vocational students in understanding the concept of Rotational Dynamics. This study used qualitative methods with 10 respondents consisting of high, medium and low categories. Instruments in this study used essay test with 6 questions and interview. The results of this study showed that students' conceptual understanding in rotational dynamics was low. Students were still having difficulties in understanding the concept of Rotational Dynamics, namely in determining angular velocity, inertia moment equation, and solving equations. Then it is better to understand the concept needs to be applied in the learning process. So it can be concluded that conceptual understanding approach needs to be applied in the learning process.